PENGARUH STRES KERJA, MOTIVASI KERJA DAN DSIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. FEDERAL INTERNASIONAL FINANCE (FIF) GROUP KABUPATEN MUKOMUKO - Deyalni Marta Kentari; Sri Ekowati (UM. Bengkulu, 2023)
This study aims to determine the effect of work stress, work motivation and work discipline on the performance of employees of PT. Federal International Finance (FIF) Mukomuko district group, either partially or simultaneously. There are several factors that will be discussed in this study, including work stress, work motivation and work discipline. The objects in this study are employees of PT. Federal International Finance (FIF) Group Mukomuko district, totaling 84 people. This type of research is quantitative research, in this study the authors used data collection methods by means of observation, interviews and distributing questionnaires. Data analysis techniques in this study, using instrument tests, classical assumption tests, analysis of respondents' responses, multiple linear regression analysis, hypothesis testing and analysis of the coefficient of determination. The results showed that work stress had a negative and significant effect on employee performance, then work motivation had a positive and significant effect on employee performance, and work discipline had a positive and significant effect on employee performance. So, from the results of the research that has been done, it can be concluded that work stress, work motivation and work discipline partially and simultaneously affect the performance of employees at PT. Federal International Finance (FIF) Mukomuko Regency Group. Keywords: Performance, Stress, Motivation, Discipline